شواهد التفاعل النقدي مع المنجز النثري الجزائري القديم فن المقامة أنموذجا - بوقردون, إيمان (جامعة الوادي - University of Eloued, 2022)
لقد وضع المنجز النثري الجزائري القديم بصمته في خارطة الإبداع العربي شأنه في ذلك شأن الآداب الأخرى بماله من خصوصية وتفرد نابع من خصوصية التجربة الإنسانية وتفردها وما يحيط بها من ملابسات تجلت أثناء الكتابة فأبانت عن مقدرة كبيرة عند أدباء الجزائر قديما ، وكان هدفنا من هذه الدراسة الوقوف عند شواهد التفاعل النقدي مع هذه المنجزات وتحديدا فن المقامة. لكنه تبين لنا أن تلقي هذه النصوص ظل باهتا ، إذ لم تأخذ حقها من الدراسة والتحليل والقراءة الفاعلة والاشتغالُ عليها لم يكن كافيا للكشف عن خصوصياتها الفكرية والفنية ، سواء في عيون النقاد المغاربة أو في مرآة الآخر العربي. Evidence of critical interaction with ancient Algerian prose Maqam is a model The ancient Algerian prose has put its mark on the map of Arab creativity, just like all the other works of literature, because of its peculiarity and uniqueness stemming from the specificity of the human experience and its surroundings, which became evident during the writing. This study demonstrated a great ability among the writers of Algeria in the past. However, it became clear to us that the reception of these texts remained lackluster, as they did not receive their right to study, analyze, read and work effectively, and were not sufficient to reveal their intellectual and artistic specificities, whether in the eyes of Moroccan critics or in the mirror of the Arab world.
مقال
Keywords: التفاعل النقدي ، النثر ، الجزائر ، المقامة; critical interaction, prose, algeria, resistance